Pijat Vimala Sebagai Terapi Komplementer Dalam Penurunan Derajat Hiperbilirubinemia Pada Neonatus Yang Menjalani Fototerapi: Studi Kasus - Tarisma Dwi Astuti; Ayuda Nia Agustina (Jurnal Ners, 2026)
Hyperbilirubinemia is a common condition in neonates that may affect growth and development if not properly managed. One potential complementary therapy is infant massage, including Vimala massage. This study aimed to describe the effect of Vimala massage on reducing the degree of hyperbilirubinemia in neonates. A descriptive case study design was used involving two neonates diagnosed with hyperbilirubinemia who also received phototherapy. Vimala massage was administered twice daily for 10 minutes over three consecutive days. The degree of jaundice was assessed using Kramer’s criteria. The results showed that both subjects experienced a reduction in jaundice severity from grade 3–4 to grade 0 by the third day. However, these outcomes may also be influenced by concurrent interventions such as phototherapy and nutritional intake. Therefore, Vimala massage may serve as a complementary therapy to support the reduction of hyperbilirubinemia in neonates. Further studies with more rigorous designs and larger sample sizes are needed to validate these findings.